2005
DOI: 10.1149/1.1864453
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Direct Electrolytic Reduction of Solid SiO[sub 2] to Si in Molten CaCl[sub 2]

Abstract: The mechanism of direct electrolytic reduction of SiO 2 in molten CaCl 2 was studied. Morphological and crystallographic investigations were conducted on Si prepared by potentiostatic electrolysis of SiO 2 contacting electrode at 1.10 V ͑vs. Ca 2+ /Ca͒ for 1 h at 1123 K. X-ray diffraction confirmed that amorphous SiO 2 was reduced to crystalline Si. From scanning electron microscopy ͑SEM͒ and energy-dispersive X-ray results, it was proved that Si columns were formed perpendicular to the reaction interface betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
121
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(134 citation statements)
references
References 19 publications
(43 reference statements)
11
121
2
Order By: Relevance
“…16,17 In this synthesis, it is found that the electrode structure plays an important role in the growth of Si NWAs. The nickel nets in the sandwich structure of the electrode (Fig.…”
mentioning
confidence: 99%
“…16,17 In this synthesis, it is found that the electrode structure plays an important role in the growth of Si NWAs. The nickel nets in the sandwich structure of the electrode (Fig.…”
mentioning
confidence: 99%
“…the 3PI mechanism explained above [17][18][19][20][21][22]27,28] . The initiation-expansion-shrinking-disappearance (IESD) process of the solid (conductive product)/solid (oxide)/liquid (electrolyte) three-phase reaction boundary (TPB), proposed to explain the electro-deoxidation of insulating compounds [29] , fits well with the deoxidation pattern of insulating SiO 2 preforms [23,[30][31][32][33] .…”
Section: Introductionmentioning
confidence: 89%
“…Therefore the released oxide ions are available in the vicinity of the reduction zone and react chemically with the adjacent unreduced SiO 2 particles in the presence of Ca 2+ ions to form CaSiO 3 (Ca 2+ + SiO 2 + O 2-→ CaSiO 3 ). Since Si is highly porous and would aid easy removal of the generated oxide ions away from the reaction site in the fully dipped condition, CaSiO 3 was not observed as an intermediate product during the electrochemical reduction of SiO 2 pellets [17,[19][20][21][23][24][25]27] .…”
Section: Intermediates During the Electrochemical Reduction Of Tio 2 mentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] In this method, electrochemical reduction of insulating SiO 2 is realized by using a SiO 2 contacting electrode, which provides a three-phase interface between the conductor, SiO 2 , and molten salt.…”
mentioning
confidence: 99%